Efficacy of EndoActivator, CanalBrush, and Passive Ultrasonic Irrigation in the Removal of Calcium Hydroxide Paste with Iodoform and p-chlorophenol from Root Canals - TARÇIN, BİLGE; TÜRKAYDIN, DİLEK; GÖKER KAMALI, SELİN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Aims: We evaluated and compared EndoActivator, CanalBrush, and passive ultrasonic irrigation (PUI) in the removal of calcium hydroxide and calcium hydroxide with iodoform and p-chlorophenol paste (Calcipast Forte) from artificial standardized grooves in the apical third of root canals. Materials and Methods: A total of 34 mandibular premolars were prepared and then split longitudinally. A standardized groove was prepared in the apical part of both segments. The grooves were filled with either calcium hydroxide or Calcipast Forte, and the segments were reassembled. CanalBrush, EndoActivator, or PUI were used. The amount of remaining medicament was evaluated using a four-grade scoring system. Results: None of the irrigation methods could completely remove the pastes from the grooves. More Calcipast Forte paste was detected compared with calcium hydroxide (P < 0.01). PUI was the least effective method in removing Calcipast Forte. Conclusions: It was more difficult to remove Calcipast Forte than a water-based calcium hydroxide paste.
Keywords: Calcipast; Calcium hydroxide; CanalBrush; Endoactivator; Iodoform; Ultrasonication; ARTIFICIAL STANDARDIZED GROOVE; XP-ENDO FINISHER; APICAL 3RD; IN-VITRO; MEDICAMENT; EFFICIENCY; DEBRIS; FILE